Studying the electronic characteristics and physisorption of OTS on the pure silver surfaces (Ag10), (Ag15) and (Ag18) - thamer, fatima; Shwya alwan, Abbas; Ali Ben Ahmed (University of Thi-Qar Journal of Science, 2023)
The interaction between organic Nano molecules and solid surfaces play a prominent role in numerous applications such as charge transfer and physisorption. Density functional theory (DFT) by utilizing sophisticated algorithms in Gaussian 09 software package at LANL2DZ, B3LYP level at the ground state energy had been utilized to attain the merits, molecular structure, contour maps density, electrostatic potentials (ESPs), density of states , infrared spectra (IR), electronic states, HOMO and LUMO energies, Energy gaps (Eg), electron affinity (E.A), ionization potential (I.P), dipole moment, the eigen values of the polarizabilities tensor αxx ,αyy and αzz , average polarizability <α> ,and symmetry to the geometrical nanostructures (Ag10), (Ag15), (Ag18), (Ag10-OTS), (Ag15-OTS) and (Ag18-OTS). Physisorption phenomena impact tremendously to the symmetry of the geometrical structure. Molecular bonds of the (σ, σ^*, π, π^*, δ and δ^*) originate because the overlap between ( s or p atomic orbitals) in the organic nanomaterials and ( d atomic orbitals) in the silver nanosurface. The distortion in contour maps interprets happening physisorption or charge transfer. According infrared spectra it can be seen new bonds because of the physisorption. Density of states diagrams demonstrates changing in the magnetic properties after physisorption. Simulation of silver (Ag) in nano dimensions make it semiconductor as compared with the bulk. The values of energy gaps of all hybrid nanostructures are in the range of semiconductor.